2018
DOI: 10.1016/j.tate.2017.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service language teachers' development of appropriate pedagogies: A transition from insightful critiques to educational insights

Abstract: This paper examines how pre-service teachers of Portuguese developed ideas about contextually appropriate pedagogies during their practicum as well as what they perceived as the impact of their pedagogical practices on student learning. The findings suggest that teacher education models which promote conscious critical reflection and teacher agency, and provide space for trainees to engage constructively both with their peers and with students are likely to generate innovative ideas for teaching which are appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Recent studies have mostly focused on a specific aspect of teachers' beliefs and its effect in ELT teaching, including creativity, aptitude, efficacy, curriculum, culture diversity, pedagogy, and teacher-child interactions (e.g., Bereczki & Kárpáti, 2018;Civitillo et al, 2018;Heyder & Brunner, 2018;Hu et al, 2017;Murphy & Torff, 2018;Sanchez et al, 2018;Thompson & Woodman, 2018). For example, Bereczki and Kárpáti (2018), in a recent review, reported that the successful implementation of creativity in education is largely dependent on teachers' own beliefs about creativity, a topic that has been investigated extensively in the past 25 years.…”
Section: Teacher Beliefs and Practices In Eltmentioning
confidence: 99%
“…Recent studies have mostly focused on a specific aspect of teachers' beliefs and its effect in ELT teaching, including creativity, aptitude, efficacy, curriculum, culture diversity, pedagogy, and teacher-child interactions (e.g., Bereczki & Kárpáti, 2018;Civitillo et al, 2018;Heyder & Brunner, 2018;Hu et al, 2017;Murphy & Torff, 2018;Sanchez et al, 2018;Thompson & Woodman, 2018). For example, Bereczki and Kárpáti (2018), in a recent review, reported that the successful implementation of creativity in education is largely dependent on teachers' own beliefs about creativity, a topic that has been investigated extensively in the past 25 years.…”
Section: Teacher Beliefs and Practices In Eltmentioning
confidence: 99%
“…For example, Walsh and Wyatt (2014) found that, while teachers' implementation of CLT was influenced by their own beliefs of CLT principles, they also adjusted their approach based on the needs and learning styles of their specific group of learners and on the pressure of achievement tests. Sanchez et al (2018) focused on pre-service language teachers' development of contextually appropriate pedagogies during their practicum in state sector schools located in peripheral urban areas. Their analysis revealed a complex interplay of internal and external factors facilitating or hindering teachers' pedagogical decisions and practices.…”
Section: Internal and External Factors Mediating Teachers' Practicesmentioning
confidence: 99%
“…International Journal of Instruction, January 2019 • Vol.12, No.1 Sanchez, Kuchah, Rodrigues & de Pietri, (2018) investigated how language trainee teachers during their teaching practice period may develop appropriate ideas for pedagogical practices and reflect on the impact of those pedagogies on students' progress. The findings of this study highlighted the importance of promoting conscious critical reflective practices and engagement of trainee teachers with their colleagues and students in generating and trying some innovative instructional ideas appropriate for their classes.…”
Section: Literature Reviewmentioning
confidence: 99%